ECO-ORIENTED ARCHITECTURE AS A MEANS OF CREATING A SUSTAINABLE URBAN ENVIRONMENT (Advances in Civil and Architectural Engineering, 2021)
Eco-oriented architecture is considered the basis for the humanization of modern. An analysis of world experience is carried out and the basic features of humanization of the urban environment are identified, considering the system-ecological approach. The eco-oriented architecture is considered a means of creating a sustainable urban environment. The features of the creation of objects in eco-oriented architecture in the twenty-first century are identified. The techniques for creating eco-oriented architectural objects in the urban environment are identified, and their sustainable development is considered. In addition, the innovative concepts and future trends in the creation of eco-oriented architectural objects are identified.